Exploring potentialities of energy-connected buildings: performance assessment of an innovative low-exergy design concept for a building heating supply system. (September 2017) - Ferrara, Maria; Coleman, James; Meggers, Forrest
Abstract: Low exergy building systems generate new possibilities for the design of high performance buildings, especially when the design of a new building is considered as part of a district where the relationship between buildings are optimized to minimize the dispersion of energy in the environment and maximize the recovery of waste energy. We present an innovative design concept and the performance assessment of the heating system of the new Embodied Computation Laboratory at Princeton University. The system is demonstrated to be able to match the heat demand without need for backup systems.